Criminal use of cryptocurrencies: a great new threat or is cash still king?. Issue 3 (2nd September 2019) - Butler, Simon
ABSTRACT: In July 2018, the Federal Reserve Chairman told the US Congress that cryptocurrencies are 'great' for money laundering. Many media headlines follow comments such as this, suggesting that cryptocurrencies are a significant criminal tool that should be feared. This article examines academic research, particularly those that analysed the Bitcoin blockchain, to see if the results matched the headlines. This was then compared to wider government and think-tank reporting. Contrary to popular opinion, this article shows that cryptocurrencies are currently used in a very small percentage of crime and they are not the great future threat that many assert. Cash is the real enemy for crime fighting and remains 'king'. It is anonymous and far more useful to criminals than cryptocurrencies. However, the future of money is uncertain and policymakers need to understand that there is more to the debate about cryptocurrencies than the headlines suggest.